Faktor-faktor yang Berhubungan dengan Kejadian Systemic Inflammatory Response Syndrome pada Pasien Hemodialisis - Zulva Safiira; Zulfachmi Wahab; Dyah Mustika; Andra Novitasari (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Background: Chronic kidney failure (CKD) is a condition of decreased kidney function for more than three months. Patients of CKD require renal replacement therapy by hemodialysis. Patients of hemodialysis often associated with Systemic Inflammatory Response Syndrome (SIRS) incidence and infection is one of the risks. Infection can develop into a dangerous event, namely sepsis. In Indonesia there were 433 cases of sepsis lead to death in hemodialysis patients. This study aims to analyze the risk facotrs that cause SIRS incidence in RS Roemani Muhammadiyah Semarang. Method: This was an observational analytic study with cross sectional design. Vascular access, age, sex, nutritional status, diabetes mellitus, hypoalbuminemia, anemia as independent variable and SIRS incidence as dependent variable. The subject in this study were all patients with a diagnosis of CKD who undergo hemodialysis treatment. This study was carried out in RS Roemani Muhammadiyah Semarang. The sampling was taken by total sampling through medical record data sources during the period January 2017 until December 20121. Statistical analysis used the Chi-Square Test for bivariat analysis and logistic regression test for multivariate.Result: Total sample obtained 46 samples. Result of bivariate test indicate that the vascular access (p=0,012); age (p=0,245); sex (p=0,332); nutritional status (p=0,457); diabetes mellitus (p=0,013); hypoalbuminemia (p=0,009); anemia (p=0,049). The Results of multivariate are known to have a strong influence on the incidence of SIRS are diabetes mellitus (p=0,035, OR=14,360) dan hypoalbuminemia (p=0,021, OR=10,167).Conclusion: There were significant correlation between vascular access, diabetes mellitus, hypoalbuminemia, anemia and SIRS incidence on hemodialysis patients. The Results of multivariate analysis showed that diabetes mellitus and hypoalbuminemia is very influential with SIRS incidence on hemodialysis patients in RS Roemani Muhammadiyah Semarang.